PENGARUH MODEL PROJECT BASED LEARNING BERBASIS DEEP LEARNING TERHADAP KETERAMPILAN MENULIS TEKS ARTIKEL ILMIAH POPULER SISWA KELAS VIII MTSN 6 KOTA PADANG - Assyifa Maulidya; Farel Olva Zuve; Amril Amir; Yulianti Rasyid (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to dedcribe three aspects : (1) the level of students’ populer scientific article writing skills in the experimental class, (2) the level of students’ populer scientific article writing skills in the control class, dan (3) the effect of Project Based Learning integrated with Deep Learning Approach on the popular scientific article writing skills of eighth-grade students at MTsN 6 Kota Padang. This research employed a uantitative approach using an experimental method with a quasi-experimental nonequevalent control group design. The population consisted of all eighth-grade students of MTsN 6 Kota Padang in the 2025/2026 academic year, totalling 447 students. The sample comprised 64 students selected through purposive sampling from two classes, VIII.12 and VIII.14, with 32 students in each class. The experimental class obtained a mean score of 88,09 (very good category), while the control class obtained 82,71 (good category. Hypothesis testing using an independent samples t-test at a 0,05 significance level with 62 degrees of freedom revealed that t-count was greater than t-table (2,18 > 1,99). Therefore, the alternative hypothesis (H1) was accepted, indicating that project based learning integrated with deep learning approach significanly influenced student populer scientific article writing skills.